2005
DOI: 10.1038/sj.onc.1208931
|View full text |Cite
|
Sign up to set email alerts
|

Defining the oncogenic function of the TEL/AML1 (ETV6/RUNX1) fusion protein in a mouse model

Abstract: The t(12;21) translocation, generating the TEL/AML1 fusion protein, is the most common genetic lesion in childhood cancer. Using a bone marrow transplantation model, we demonstrate that TEL/AML1 expression impinges on normal hematopoietic differentiation, leading to the in vivo accumulation and persistence of an early progenitor compartment with a Sca1 þ /Kit hi /CD11b þ phenotype and an increased self-renewal capacity, as documented by replating assays in vitro. Differentiation of these cells is not blocked, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
54
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 64 publications
5
54
1
Order By: Relevance
“…Thus, we demonstrated that TEL-AML1 enhanced the self-renewal capacity of B-cell progenitors in colony-forming assays in vitro and conferred a competitive advantage on hematopoietic reconstitution in vivo (Morrow et al, 2004). Other studies observed an accumulation of early B-cell progenitors expressing TEL-AML1 (Tsuzuki et al, 2004;Fischer et al, 2005). To understand further the mechanism of TEL-AML1 action, we have analysed the activity of TEL-AML1 deletion mutants in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 86%
“…Thus, we demonstrated that TEL-AML1 enhanced the self-renewal capacity of B-cell progenitors in colony-forming assays in vitro and conferred a competitive advantage on hematopoietic reconstitution in vivo (Morrow et al, 2004). Other studies observed an accumulation of early B-cell progenitors expressing TEL-AML1 (Tsuzuki et al, 2004;Fischer et al, 2005). To understand further the mechanism of TEL-AML1 action, we have analysed the activity of TEL-AML1 deletion mutants in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 86%
“…7,8 Several lines of evidence suggest that ETV6/RUNX1 is not sufficient for leukemic transformation, such as detection of the gene fusion in Guthrie cards from patients who later developed ETV6/RUNX1-positive ALLs, 9 identical gene fusions in twins with concordant leukemia, 10 identification of the chimeric transcript in normal cord blood samples 11 and lack of leukemia in mouse models. 12 Thus, although t(12;21)-positive preleukemic clones, at least in some cases, arise already in utero, additional mutations are most likely required for overt leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…This initiating event, seen as early as in utero (Wiemels et al, 1999;Hjalgrim et al, 2002), most likely requires additional genetic changes in order to lead to leukaemia e.g. ETV6/RUNX1 transcripts have been demonstrated in normal cord blood samples at low levels (Mori et al, 2002;Lausten-Thomsen et al, 2011) and neither ETV6/ RUNX1-positive knock-in mouse models nor carriers of ETV6/RUNX1-positive pre-leukaemic cells will all develop leukaemia (Fischer et al, 2005;Hong et al, 2008). Thus, the development of ETV6/RUNX1-positive leukaemia requires one or more secondary genetic changes and previous studies have indeed shown additional genetic changes in the majority of ETV6/RUNX1-positive childhood ALL patients (Forestier et al, 2007;Mullighan et al, 2007;Kawamata et al, 2008;Lilljebjorn et al, 2007Lilljebjorn et al, , 2010Parker et al, 2008;Mullighan et al, 2008;van Delft et al, 2011).…”
mentioning
confidence: 99%